2011
DOI: 10.1111/j.1365-2249.2011.04494.x
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of the adaptor protein Nck1 in Jurkat T cell activation and function

Abstract: SummaryThe non-catalytic region of tyrosine kinase (Nck) is proposed to play an essential role in T cell activation. However, evidence based on functional and biochemical studies has brought into question the critical function of Nck. Therefore, the aim of the present work was to investigate the role of Nck in T cell activation. To study this, the human Jurkat T cell line was used as a model for human T lymphocytes. The short interfering (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 39 publications
2
27
0
Order By: Relevance
“…2) with opposing associations in CLL ( P 1-tailed  = 1.97 × 10 −8 ) and HL ( P 1-tailed  = 3.31 × 10 −3 ). rs11715604 maps to intron 1 of NCK1, which is integral to T-cell activation3839 and regulates the PI3K/Akt pathway40. We also identified a number of promising associations that did not reach genome-wide significance, but exhibited moderate effects in the different BCM (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…2) with opposing associations in CLL ( P 1-tailed  = 1.97 × 10 −8 ) and HL ( P 1-tailed  = 3.31 × 10 −3 ). rs11715604 maps to intron 1 of NCK1, which is integral to T-cell activation3839 and regulates the PI3K/Akt pathway40. We also identified a number of promising associations that did not reach genome-wide significance, but exhibited moderate effects in the different BCM (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The siRNA sequence targeting Nck1 used in this study was 5 -GGGTTCTCTGTCAGAGAAA -3 . The siRNA transfection was performed as previously described 14 . Briefly, 2 × 10 5 Jurkat cells were harvested, washed with D-PBS (Invitrogen) and resuspended in 10 µl solution R plus 50 pmol of stealth RNAi siRNA duplexes specific for Nck1.…”
Section: Nck Sirna Transfectionmentioning
confidence: 99%
“…In many cell types, Nck links phosphotyrosine signals and regulates actin cytoskeletal rearrangements 7 . In T cells activated via their T cell antigen receptor (TCR), Nck is essential in regulating actin rearrangement and immunological synapse formation [8][9][10][11][12][13][14] . Interestingly, our recent data have shown that silencing of Nck1 by transfection of siRNA to Jurkat T cell results in abrogation of T cell activation as indicated by decreased interleukin-2 (IL-2) secretion and CD69 expression 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Bone marrow reconstitution with CD3ε PRS mutants in CD3ε-deficient mice, Nck overexpression in primary T cells, Nck knockout mice, and PRS knockin (KI) mice have all been used to study the role of the PRS and Nck in T cell development and mature T cell activation (14)(15)(16)(17)(18)(19)(20). Some experiments have suggested that the PRS is important for thymic maturation, but not for mature T cell activation in vitro (15), although experiments with bone marrow chimeras indicate that the PRS is important to activate mature T cells by weak, but not by strong, agonists in vitro (19).…”
mentioning
confidence: 99%